Short Fimbriae of Porphyromonas gingivalis and Their Role in Coadhesion with Streptococcus gordonii - Yoonsuk Park; Maria Regina Lorenzetti Simionato; Kachiko Sekiya; Yukitaka MURAKAMI; Deanna James; Chen Weibin; Murray Hackett; Fuminobu Yoshimura; Donald R. Demuth; Richard J. Lamont (2005)
ABSTRACT Porphyromonas gingivalis , one of the causative agents of adult periodontitis, attaches and forms biofilms on substrata of Streptococcus gordonii . Coadhesion and biofilm development between these organisms requires the interaction of the short fimbriae of P. gingivalis with the SspB streptococcal surface polypeptide. In this study we investigated the structure and binding activities of the short fimbriae of P. gingivalis . Electron microscopy showed that isolated short fimbriae have an average length of 103 nm and exhibit a helical structure with a pitch of ca. 27 nm. Mfa1, the major protein subunit of the short fimbriae, bound to SspB protein, and this reaction was inhibited by purified recombinant Mfa1 and monospecifc anti-Mfa1 serum in a dose-dependent manner. Complementation of a polar Mfa1 mutant with the mfa1 gene restored the coadhesion phenotype of P. gingivalis . Hence, the Mfa1 structural fimbrial subunit does not require accessory proteins for binding to SspB. Furthermore, the interaction of Mfa1 with SspB is necessary for optimal coadhesion between P. gingivalis and S. gordonii .